Behavioral intention towards financial statement fraud: application of theory planned behavior / Nuriffah Azmi, Noreena Md Yusoff and Rina Fadhilah Ismail - Azmi, Nuriffah; Md Yusoff, Noreena; Ismail, Rina Fadhilah (Faculty of Accountancy, 2019)
The rising rates of financial statement fraud committed over the years as reported are alarming and largely associated with the behavioral intention of the individuals. One of the prevalent fraud cases that happened is when financial records are falsified, manipulated or altered. It has been done by accounting professionals and therefore, there is a need to identify the factors that drive them to commit such fraud. This study used planned behavioral theory in order to improvise the detection measure by using the three elements in the theory namely, attitude towards behaviors, subjective norms and perceived behavioral control. The data were collected through questionnaires shows that there is a significant relationship between attitudes towards behavior and perceived behavioral control against behavioral intention of committing such fraud. It suggests that accounting professionals should behave like a professional and hinder themselves from committing financial statement fraud. From the findings, it was expected to give a great awareness particularly to accounting professionals and specifically to the organizations on the importance of having good ethical behavior, thus they may come up with more aggressive fraud detection and prevention plan.